Characteristic of Prehistoric Austronesian Pottery Around Lake Singkarak, Solok, West Sumatra - Nenggih Susilowati (KALPATARU, 2023)
The karst environment with forests and lakes has the potential to be a source of water, food, and materials that are important to the human's ideal location for its inhabitants. Pottery shards found in surveys and excavations illustrate that the site became a place to settle with various human activities. This article aims to determine the characteristics of Austronesian pottery remains at the cave and open sites and determine the relationship with maritime culture around Lake Singkarak. The method used is qualitative, analyzing pottery fragments supported by laboratory analysis. The results of the analysis data note that the discovery of geometric patterns and red slips can illustrate the expertise of supporters in beautifying pottery and describe the cultural history and life of the makers.